Beyond Representation of Women in I-O to Producing Gender-Inclusive Knowledge. Issue 3 (20th September 2018) - Stockdale, Margaret S.; Eagly, Alice H.
Abstract : Gardner, Ryan, and Snoeyink (2018 ) provided an excellent and much-needed analysis of the status of women in industrial and organizational (I-O) psychology. Although others have produced overall assessments of the status of women in psychology (Eagly & Riger, 2014 ; Kite et al., 2001 ), these are not sufficient to identify conditions within the subfields of psychology. As shown by statistics on the divisions of the American Psychological Association (http://www.apa.org/about/division/officers/services/profiles.aspx ), the subfields differ greatly in their gender balance, with some being male dominated (e.g., experimental and cognitive science), others female dominated (e.g., developmental psychology), and still others representing women and men more equally (e.g., social and personality psychology). I-O psychology is among the more gender-balanced fields, with an increasing proportion of women over time. It would seem that I-O's gradual inclusion of more women should have changed aspects of research and discourse in this field. In this comment, we argue that these women have produced impressive changes.